Dynamic Service Restoration of Distribution Networks With Volt-Var Devices, Distributed Energy Resources, and Energy Storage Systems - Carrion, Cesar E. C.; Faria, Wandry R.; MacEdo, Leonardo H. [UNESP]; Romero, Ruben [UNESP]; Pereira, Benvindo R. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The new energy resources in distribution systems have led researchers to consider the operation of such elements during service restoration. Hence, the current state-of-the-art regarding the restoration problem considers the operation of distributed resources in both island and grid-connected modes. Few articles also address the system's restoration capacity changes throughout the time needed to repair the network after an outage, given the variations in the system's demand and availability of energy sources. However, the solutions proposed in the literature converge in proposing a single topology that is feasible throughout the entire repairing time. In this article, we propose addressing the mutable nature of the system's restoration capacity by splitting the repairing time into several time intervals and associating each of them with a specific configuration that minimizes the out-of-service load. Energy storage systems, intermittent and dispatchable generators, and voltage-control devices are also considered. The problem is formulated as a mixed-integer linear programming (MILP). The model and its scalability are tested using the 53-, 217-, and 404-node systems, considering different fault scenarios and reliability indices. The results show that the nonsupplied energy during the repairing time decreases when dynamic changes in the system topology are considered. Furthermore, the effects of storage systems operation and their integration with dynamic topology changes are highlighted.
Keywords: Distribution systems operation; MILP; Optimization; Reliability; Resilience